OPTIMASI PROSES DEASIDIFIKASI DALAM PEMURNIAN MINYAK SAWIT MERAH SKALA PILOT PLANT [Optimization of Deacidification Process in Red Palm Oil Purification on Pilot Plant Scale] - I Wayan Rai Widarta; Nuri Andarwulan; Tri Haryati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
Deacidification is one of the steps in palm oil refining process which aims to separate free fatty acids formed during post-harvest handling. It is carried out using alkali solution such as NaOH (sodium hydroxide). Carotenoids in palm oil are affected by this step. Therefore, deacidification has to be controlled to minimize the destruction of carotenoids during processing. The objective of this research was to improve deacidification process in pilot plant scale so that the process can produce lower level of free fatty acids (FFA) and higher recovery of carotene in high yield neutralized red palm oil (NRPO). Characterization of physical and chemical properties of crude palm oil (CPO) such as moisture content, FFA and carotene contents, saponification number, iodine value, peroxide value, and color were determined before processing. Degumming was performed before deacidification process. The 17.5% excess of NaOH was obtained from the pilot plant scale deacidification trial. The optimization of deacidification time and temperature was carried out by using central composite design (CCD). Response surface method (RSM) was used to observe the influence of treatments on the FFA level reduction, carotene recovery, and NRPO yield. The result showed that the optimum deacidification condition was at 61 ± 2°C in 26 minutes, and at the 16°Be NaOH strength with 17.5% excess of NaOH. In this optimum condition, the process achieved 96.35% of FFA reduction, 87.30% of carotene recovery, and 90.16% of NRPO yield.